Radiosurgery and stereotactic radiotherapy with cyberknife system for meningioma treatment. Issue 1 (February 2018) - Di Franco, Rossella; Borzillo, Valentina; Ravo, Vincenzo; Falivene, Sara; Romano, Francesco Jacopo; Muto, Matteo; Cammarota, Fabrizio; Totaro, Giuseppe; Ametrano, Gianluca; Rossetti, Sabrina; Cavaliere, Carla; D' Aniello, Carmine; et al.
Objective: The aim of this work was to evaluate the impact of stereotactic radiosurgery/fractionated stereotactic radiotherapy with the Cyberknife system on local disease control, clinical outcome and toxicity in patients with meningioma, according to the site and histological grade of lesion. From January 2013 to April 2017, 52 patients with intracranial meningiomas were treated with the Cyberknife system. Twenty-four patients had undergone previous surgery: 38% gross total resection, 10% subtotal resection; 27 patients underwent no surgery; 22 patients had a recurrence of meningioma. Methods: Radiosurgery was used for lesions smaller than 2 cm, stereotactic radiotherapy for lesions larger than 2 cm, or smaller but close to a critical site such as the optical chiasm, optic pathway or brainstem. Results: Local control and clinical outcomes were analysed. Median follow-up was 20 months: six patients died, one after re-surgery died from post-surgical sepsis, three from heart disease. Progression-free survival had a mean value of 38.3 months and overall survival of 41.6 months. We evaluated at 12 months 28 patients (100% local control); at 24 months 19 patients (89% local control); at 36 months nine patients (89% local control). At baseline, 44/52 patients (85%) were symptomatic: 19 visual disorders, 17 motor disorders, six hearing disorders, 10 headache and six epilepsy. Visual symptoms remained unchanged in 52%, improved in 32%, resolved in 16%. Headache was improved in 40%, resolved in 10%, unchanged in 50%. Epilepsy was resolved in 17%, unchanged in 33%, worsened in 33%. Conclusions: Stereotactic radiosurgery/fractionated stereotactic radiotherapy with Cyberknife provides a good local disease control, improving visual, hearing and motor symptoms.